“Bridging the digital divide”: Assessing and advancing teachers’ digital literacy across Indonesian provinces - Zulaikha, Siti; Fadholi, Muhamad; Sururi, Sururi; Syahril, Syahril; Jamil, Soraya Nuron; Ariyanti, Putri Novira (UIN Raden Mas Said Surakarta, 2025)
Amid the accelerating integration of digital technologies into educational ecosystems, a critical gap remains in the systematic evaluation and strategic enhancement of teachers’ digital literacy across Indonesia’s diverse regions. This encourages the pressing need for validated assessment instruments and targeted interventions to support educators' competencies. This study disseminates a rigorously validated digital literacy measurement tool grounded in the Instant Digital Competence Assessment (IDCA) framework and investigates the digital literacy levels of elementary school teachers in several provinces of Indonesia, i.e., DKI Jakarta, West Java, and West Sumatra. Employing a quantitative-descriptive survey design, data were collected from 296 teachers through online questionnaires. The sample size was calculated using Slovin’s formula with a 10% margin of error, followed by simple random sampling for participant recruitment. The IDCA instrument measures digital literacy across three core dimensions: Technological, Cognitive, and Ethical. The findings reveal that teachers generally exhibit a